On the structure of resolvent of singularly perturbed operator solving the problem of eigenvalues - Koshmanenko, V. D.; Tuhai, H. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We investigate the structure of the resolvent of a singularly perturbed operator of finite rank that solves an eigenvalue problem.